Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-27T14:30:55+02:00
2⅓ + 3* ⅔=2⅓ +2= 4 ⅓

(4,4-2) * ⅝=2,2* ⅝=¹¹/₅*⅝=¹¹/₈=1 ⅜

⅘ +2,4 : 0,4 - 0,2=⅘+6-0,2=0,8+6-0,2=6,8-0,2=6,6

10⅔ - 2⅓+ ⅔=8⅓+⅔=9

3,6 * ⁵/₁₂ - ½ *3=¹⁸/₅*⁵/₁₂-³/₂=¹⁸/₁₂-³/₂=1,5-1,5=0

(12-3,6:2)*4=(12-1,8)*4=10,2*4=40,8
1 5 1
2009-09-27T14:47:56+02:00
2⅓ + 3ײ/₃= 2⅓ + 2= 4⅓
(4,4-2) × ⅝= 2⅖ × ⅝= ¹²/₅ × ⅝= ¾
⅘ +2,4 ÷ 0,4 - 0,2= ⅘ + 6- 0,2= 6,8- 0,2= 6,6
10⅔ - 2⅓+ ⅔=10⅔- 3= 7⅔
3,6 × ⁵/₁₂ - ½ ×3= ¹⁸/₅ × ⁵/₁₂ -1½= 1½ -1½= 0
(12-3,6 ÷2)× 4= (12- 1,8)× 4= 10,2× 4= 40,8
  • Użytkownik Zadane
2009-09-27T14:51:52+02:00
2⅓ + 3ײ/₃= 2⅓ + 2= 4⅓
(4,4-2) × ⅝= 2⅖ × ⅝= ¹²/₅ × ⅝= ¾
⅘ +2,4 ÷ 0,4 - 0,2= ⅘ + 6- 0,2= 6,8- 0,2= 6,6
10⅔ - 2⅓+ ⅔=10⅔- 3= 7⅔
3,6 × ⁵/₁₂ - ½ ×3= ¹⁸/₅ × ⁵/₁₂ -1½= 1½ -1½= 0
(12-3,6 ÷2)× 4= (12- 1,8)× 4= 10,2× 4= 40,8